A mixed methods exploration of motor imagery in autistic and non-autistic adults: Diverse experiences and implications for interventions - Molly Brillinger; Ying Bai; April Karlinsky; Timothy N. Welsh; Ellen Poliakoff; Emma Gowen (PLoS ONE, 2025)
Research on motor imagery (MI) in non-autistic individuals suggests that there are shared neural circuitries between imagery and execution. The relationship between imagined and executed movements, and the use of MI in autistic adults is poorly understood. This study explored MI comprehension, prior use of MI, and subjective experiences during MI in autistic and non-autistic adults. Twenty autistic and twenty non-autistic individuals responded to a series of questions probing their understanding of and engagement in MI. Participants then completed the Kinesthetic and Visual Imagery Questionnaire (KVIQ), and reported on their subjective experiences during MI. Although there were no differences between the autistic and non-autistic individuals in their understanding of MI, the non-autistic group may have more prior use of MI in their everyday lives. Additionally, autistic participants generally reported less vivid imagery on the KVIQ compared to non-autistic participants, however experiences during MI varied widely across both groups ranging from vivid/intense images/sensations to the inability to imagine. In summary, some autistic individuals are able to engage in MI, but, similar to their non-autistic peers, MI ability and experiences vary across individuals. This work has important implications for MI interventions aimed at improving motor coordination.